Changes in the proteome of sea urchin Paracentrotus lividus coelomocytes in response to LPS injection into the body cavity - Inguglia, Luigi (PLoS One, 2020)
BACKGROUND: The immune system of echinoderm sea urchins is characterised by a high degree of complexity that is not completely understood. The Mediterranean sea urchin Paracentrotus lividus coelomocytes mediate immune responses through phagocytosis, encapsulation of non-self particles, and production of diffusible factors including antimicrobial molecules. Details of these processes, and molecular pathways driving these mechanisms, are still to be fully elucidated. PRINCIPAL FINDINGS: In the present study we treated the sea urchin P. lividus with the bacterial lipopolysaccharide (LPS) and collected coelomocytes at different time-points (1, 3, 6 and 24 hours). We have shown, using label-free quantitative mass spectrometry, how LPS is able to modulate the coelomocyte proteome and to effect cellular pathways, such as endocytosis and phagocytosis, as soon as the immunomodulating agent is injected. The present study has also shown that treatment can modulate various cellular processes such as cytoskeleton reorganisation, and stress and energetic homeostasis. CONCLUSIONS: Our data demonstrates, through mass spectrometry and the following functional annotation bioinformatics analysis, how the bacterial wall constituent is sufficient to set off an immune response inducing cytoskeleton reorganisation, the appearance of clusters of heat shock proteins (Hsp) and histone proteins and the activation of the endocytic and phagocytic pathways. Data are available via ProteomeXchange with identifier PXD008439.